Performance evaluation of Mung bean [Vigna radiata (L.) Wilczek] varieties in pastoral areas of South Omo Zone, Southern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Field experiments were conducted on pastoral and agro-pastoral areas of South Omo Zone at Dasenech, Hammer and Gynagatom woredas of Southern Ethiopia on mung bean [Vigna radiata (L.) Wilczek] varieties in 2019 under irrigated condition. The objective of the study was to select the best performing mung bean varieties in the target areas. The treatments involved in the study were three improved and one local mung bean variety (NVL-01, Shewarobit, N-26, and local). The experiment was carried out using a randomized complete block design (RCBD) with three replications. The combined analysis of variance result for mean squares depicted that there were significant differences observed among the varieties for all the studied parameters except the number of seeds per pod. The overall mean values for plant height ranged from 41.33 cm for Shewarobit to 62.00 cm for the local check. The mean values for the number of pods per plant ranged from 19.33 for the local check to 24.44 for NVL-01. The mean value for a thousand seeds weight was maximum 59.56 g for N-26, while it was a minimum 48.22 g for Shewarobit. The highest overall mean grain yield of 2483.8 kg ha-1 was recorded for N-26 while the minimum 1462.6 kg ha-1 was noted for the local check. The grain yield advantages of 41.11, 34.52, and 25.26% were obtained from the improved varieties N-26, NVL-01, and Shewarobit, respectively over the local check. The effect of varieties on grain yield was significant and the best performing mung bean varieties namely N-26 2483.8 kg ha-1 and NVL-01 2233.6 kg ha-1 would be recommended for the specific community and its vicinity even though further study should be carried out including some recently released varieties for improved mung bean production and also to put the recommendation on a strong basis.Int. J. Agril. Res. Innov. Tech. 12(1): 141-144, June 2022